Integrating Maqashid al-Shariah into Islamic Economic Practices: A Contemporary Analytical Framework and Its Applications - Marwah, Andi; bin Sapa, Nasrullah; Syatar, Abdul (El-kahfi | Jurnal Ekonomi Islam, 2025)
The growing demand for ethical and inclusive economic frameworks has renewed scholarly interest in maqasid al-shariah as a foundational paradigm in Islamic economics. As the higher objectives of Islamic law, maqasid seek to protect religion (din), life (nafs), intellect (aql), lineage (nasl), and wealth (mal). This study employs a qualitative-descriptive approach using structured library research to analyze fifteen academic sources published between 2019 and 2025, focusing on how maqasid principles are conceptualized and implemented in Islamic finance, social policy, and cooperative systems. The findings reveal that while there is growing theoretical engagement with maqasid, practical applications remain limited by formalistic interpretations and insufficient institutional adaptation. Notable progress exists in areas such as mudharabah, takaful, and zakat-waqf integration, but broader reform is needed to shift from legal compliance to maqasid-oriented innovation. This research contributes to the theoretical advancement of Islamic economic thought by offering a synthesized and critical review of contemporary maqasid applications, and recommends the systemic integration of maqasid into policy-making, institutional governance, and economic design.